Roberto Arlt, photographer. On aguafuertes fluviales, patagónicas y españolas (Anclajes, 2016)
This article seeks to explore the link between chronicle and photography in three of Roberto Arlt’s trips as a correspondent for the Spanish newspaper, El Mundo: his travels through the Littoral and Patagonian regions of Argentina as well as his great journey across Spain. Our main purpose is to analyze the way in which the writer, for the first time, unites image with text by including landscapes and scenic views in his journalistic work. Moreover, we will examine what types of aesthetic transformations occur in the collection of photographs taken by Arlt himself, and if, indeed, the images captured during his travels across Argentina favor nature views by means of wide shots while the images from Spain depict architecture, more complex aesthetic compositions, and portraits. The three journeys will therefore be studied together to analyze Roberto Arlt’s role both as a writer and a photographer and the way in which the intermedial analysis of chronicle and image contributes to the study of the author’s journalistic work.
Keywords: Roberto Arlt; Argentinean literature; intermediality; twentieth century; journey